(untitled) (RuMoRes, 2010)
The language of video has been influencing the language of film; also, the relationship between cinema and video has been discussed by different authors. Based on these discussions, such as Arlindo Machado´s Pré-cinemas e pós-cinemas (1997) and A televisão levada a sério (2001), and Philippe Dubois’s, in Cinema, video, Godard (2004), as well as Raymond Bellour’s, in L’entre-images (1997), the article verifies how the language of video brought together the language of film and the language of music videoclips, and vice versa. In this context we want to analyze the encounter and the relationships between video, music videoclips and cinema. And identify the elements that bring these languages together, contributing to the best understanding of contemporary tendencies.